Hyaluronic acid-oleylamine and chitosan-oleic acid conjugate-based hybrid nanoparticle delivery via. dissolving microneedles for enhanced treatment efficacy in localized breast cancer - Jha A.; Kumar M.; Goswami P.; Manjit M.; Bharti K.; Koch B.; Mishra B. (My University, 2025)
Microneedle technology offers a minimally invasive treatment strategy to deliver chemotherapeutics to localized tumors. Amalgamating the surface functionalized nanoparticles with microneedle technology can potentially deliver drugs directly to tumors and subsequently target cancer cells via, overexpressed receptors on the cell surface, thereby enhancing the treatment efficacy while reducing side effects. Here, we report cetuximab anchored hyaluronic acid-oleylamine and chitosan-oleic acid-based hybrid nanoparticle (HA-OA/CS-OA NPT)-loaded dissolving microneedles (MN) for targeted delivery of cabazitaxel (CBT) in localized breast cancer tumor. The HA-OA/CS-OA NPT was characterized for their size, surface charge, morphology, physicochemical characteristics, drug release behavior, and in vitro anti-cancer efficacy. The HA-OA/CS-OA NPT were of ~125 nm size, showed enhanced cytotoxicity and cellular uptake, and elicited a superior apoptotic response against MDA-MB-231 cells. Subsequently, the morphology and physicochemical characteristics of HA-OA/CS-OA NPT-loaded MN were also evaluated. The fabricated microneedles were of ~550 μm height and showed loading of nanoparticles equivalent to ~250 μg of CBT. The ex vivo skin permeation study revealed fast dissolution of microneedles upon hydration, while the drug permeation across the skin exhibited ~4-fold improvement in comparison to free drug-loaded MN. In vivo studies performed on DMBA-induced breast cancer in female SD rats showed a marked reduction in tumor volume after administration of drug and nanoparticle-loaded microneedles in comparison to intravenous administration of free drug. However, the HA-OA/CS-OA NPT-MN showed the highest tumor reduction and survival rate, with the lowest body weight reduction in comparison to other treatment groups, indicating its superior efficacy and low systemic toxicity. Overall, the dissolving microneedle-mediated delivery of targeted nanoparticles loaded with chemotherapeutics offers a superior alternative to conventional intravenous chemotherapy. © 2024 Elsevier B.V.